(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The process of forming Islāmic values requires an answer to such fundamental questions as who the child is, how to educate him, what is the essence of Islāmic values, when and what values need to be educated. To form a deeply convinced person, Islāmic values must be educated in him. From time immemorial, values have been formed in Uzbekistan related to the process of forming a child, to protecting the child in the family and society. These values developed in the national consciousness. Therefore, the issue of the formation of Islāmic values in the Uzbek family is considered from the perspective of the process of upbringing and education, from the perspective of personality formation.